Phonetic Study: The Use of Diction in Short Story Essays of Class XI Students of SMA Negeri 10 Depok - Sri Sumarsih; Irwan Siagian (Syntax Corporation Indonesia, 2023)
The aim of the research was to find out the diction used by students in composing short stories. The research method used is descriptive qualitative method. The data source for this research was short stories written by students of class XI at SMA Negeri 10 Depok in the 2021/2022 academic year. The results of the study obtained 10 requirements for the accuracy of the use of diction using the percentage technique. Based on the research conducted by the researcher, 81 data were obtained from 42 students' short story essays. Of the 10 types of diction accuracy requirements analyzed, the results of inaccurate use of diction were as follows: use of general and special words 11.11%, use of connotative and denotative words 27.16%, use of almost synonymous words 35.81%, use of idioms 4.93%, continuity of word choice 11.11 %, and the use of the word senses 9.87%. From the results obtained, it can be concluded that class XI students used a lot of synonymous diction in the short story essays they made and only a few found inaccuracies, most of them were correct and appropriate for their use in short story essays.